Staphylococcal infections among leukemic patients (Baghdad Science Journal, 2012)
Staphylococcus are cause hospital community acquired infection and they are an important cause of health –care associated infection.The Coagulase positive Staphylococcus are Staphylococcus aureus which can implicated in toxic shock syndrome. Methicillin and Vancomycin Staphylococcus aureus resistant (MRSA, VRSA) become major cause of hospital- acquired infection and community acquired infection.Coagulase negative staphylococcus emerged as major cause of infection in immunocompromised patients.The main objective of this study was to evaluate the distribution of Staphylococci among leukemic patients since it is well known that leukemic patients are prone to be infected easily due to their immunosuppressed status.This study was undertaken between oct. 2009 and Jun 2010 at Iraqi center of hematology and medical genetics. 140 clinical specimen(aspirated wound,superficial wound,urine, blood) have deen collected carefully from leukemic patients and subjected to well known established microbiological methods for diagnosis and identification of the isolates .All isolates were tested for their susceptibility to antimicrobials according to Kirby –Bauer technique.Out of 140 clinical specimen collected from leukemic patients, it was possible to obtain( 63) bacterial isolates form which(43) of Coagulase negative staphylococci (CONS) and (20) of Coagulase positive staphylococci. Out of 43(CONS) isolates has been found that S.epidermidis constitutes (28)the highest of all isolates. Antimicrobial susceptibility reveald that S.aureus is highly sensitive to Gentamycin (85%), Erythromycin (80%), while it is resistant to the drugs Cefotaxim (45%), Choramphenicol(40%),and Tetracycline(20%). S.epidermidis show highly sensitive to Erythromycin(100%),Vancomycin (100%), and Cefotaxim(70%) and highly resistant to the drugs Chloromphenicol(45%), Augmentin(45%),Gentamycin (10%), and Tetracycline(10%).It is concluded that S.epidemidis rankes the first( 28)among the isolates and S.aureus ranke the 2nd .All isolates were highly resistant to Chloramphenicol and highly sensitive to Erythromycine.